Peculiarities of the formation of a hardened layer during laser borinizing of piston rings - Hlushkova, D.B.; Ryzhkov, Y.V.; Kalinina, N.E.; Nosova, T.V. (Вопросы атомной науки и техники, 2022)
Insufficient wear resistance of piston ring materials often limits the growth of machine productivity and service life. The use of traditional drilling methods associated with the diffusion of boron into the solid phase will lead to the formation of a working layer with high fragility. Therefore, the problem of increasing the wear resistance of piston rings without embrittlement is relevant. The use of laser heating during drilling provides the formation of a new layer with special properties. However, optimal properties can only be achieved after the relationship between the process parameters and the depth of the bored layer has been established. The influence of laser heating parameters on the composition and depth of the drilling layer is established in the work. The results of research can be extended to other parts that are subject to intensive wear.